Genetic ablation of interleukin-17A augments fibrosis in a mouse model of cholestatic liver injury - Takashi Kitagataya; Anuradha Krishnan; Kirsta E. Olson; Florencia Gutierrez; Michelle Baez-Faria; Maria Eugenia Guicciardi; Kevin D. Pavelko; Adiba I. Azad; Gregory J. Gores (PLoS ONE, 2026)
Aim The underlying mechanisms contributing to cholestatic liver injury remain unclear. The pro-inflammatory leukocyte-restricted cytokine interleukin-17A (IL-17A) has been implicated in human cholestatic liver injury. However, mechanistic insights are lacking and require further exploration in preclinical models. Herein, we examined the effect of IL-17A genetic ablation in a mouse model of cholestatic liver injury. Method Age and gender-matched littermate wild type (WT) and Il-17a -/- C57BL/6 mice were fed an intermittent 0.1% 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet for 21 days to induce cholestatic liver injury or a control diet. Results As compared to WT littermates, Il-17a -/- mice displayed more abundant desmin-positive myofibroblasts and increased fibrosis. NanoString analysis of intrahepatic leukocyte populations using a fibrosis-related gene panel identified upregulation of Tnfsf14 (encoding the protein LIGHT) in the DDC-fed Il-17a -/- mice. Although mass cytometry identified an increase in myeloid cells in both genotypes of the DDC-fed mice, we could not identify LIGHT expression in this cell lineage. Instead, the upregulation of LIGHT expression was largely restricted to a CD4 + T cell population as assessed by flow cytometry. Enhanced LIGHT expression was observed in a Th1 + CD4 + T cell population. LIGHT activated primary human hepatic stellate cells in vitro, suggesting that LIGHT stimulation of hepatic fibrogenesis may be direct. Conclusion Taken together, these data suggest that IL-17A restrains expression of the profibrogenic cytokine, LIGHT, by Th1-polarized CD4 + T cells, and implicate a role for LIGHT in cholestatic fibrogenesis in DDC-fed mice; a finding which requires validation in additional models.